Determination of Benzalkonium Chloride in Ophthalmic Solutions by Stability-Indicating HPLC Method: Application to a Stability Study - Hashem AlAani, Yasmin AlNukkary (Journal of Applied Pharmaceutical Science, 2016)
A simple HPLC method for determination of Benzalkonium chloride in various ophthalmic solutions was developed. The chromatographic analysis was achieved using CN column (250 mm, 4.6 mm i.d., 5 μm) with isocratic mobile phase consisting of acetonitrile - phosphate buffer (pH 5.5; 0.05 M) (70:30, v/v) at a flow rate of 1 mL/minute. The column temperature was maintained at 25°C and the detection wavelength was 210 nm. The proposed HPLC method was successfully validated according to the ICH guideline and proved to be stability-indicating. This method was applied to quantify Benzalkonium chloride during in-use stability study of two ophthalmic solutions. Antimicrobial effectiveness of Benzalkonium chloride in these solutions was also evaluated. The developed method is suitable for the routine analysis of Benzalkonium chloride in many ophthalmic solutions as well as for the stability studies.
Keywords: Benzalkonium chloride, Ophthalmic solutions, HPLC, Stability-indicating, In-use stability.